eLearning Gamification Prototype Development using User Centered Design Approach - Satria, Deki (Universitas Muhammadiyah Magelang, 2023)
Abstract eLearning is one of the tools used by the educational institution. Unfortunately, many eLearning systems were not fully utilized by the user. These problems occur because of a lack of interaction in the eLearning system, dulling the learning process. Another problem is the lack of preparation from the user. This research tried to tackle these problems using gamification. The gamification adopted in this prototype is Medals, Ratings, and Discussion. The development prototype development using User Centred Design to gather the requirements and system flows. The use of these elements is hoped to be able to elevate the eLearning adoptions. The results of this research are the prototype of the gamification features and the business process of discussion in the eLearning system